Effectiveness of acupuncture for patients with vascular dementia: A systematic review and meta-analysis - Yinghua Chen; Haoyu Wang; Zhongren Sun; Xiaoqing Su; Ruiqi Qin; Junfeng Li; Wei Sun (Elsevier, 2022)
Objectives: This meta-analysis assessed the treatment effectiveness of acupuncture in patients with vascular dementia. Methods: The PubMed, Embase, Cochrane library, and China National Knowledge Infrastructure were searched to identify eligible randomized controlled trials (RCTs). The odds ratios (ORs) and weighted mean differences (WMDs) with 95 % confidence intervals (CIs) were used to assess the pooled effect estimates using a random-effects model for categorical and continuous outcomes, respectively. Results: Thirty-four RCTs (2672 patients) were selected for the final meta-analysis. The use of acupuncture showed association with an increased incidence of effective rate (OR: 3.28; 95 % CI: 2.54-4.24; P < 0.001). The pooled WMDs revealed that acupuncture was significantly associated with an improvement in the Hasegawa dementia scale (HDS) (WMD: 4.31; 95 % CI: 3.15-5.47; P < 0.001), and Mini-Mental State Examination scores (MMSE) (WMD: 3.07; 95 % CI: 2.40-3.74; P < 0.001). However, the use of acupuncture showed no association with the level of Activities of daily living (ADL) (WMD: 1.93; 95 % CI: − 2.53 to 6.38; P = 0.397). Finally, acupuncture was associated with lower levels of Scale for the differentiation of syndromes of vascular dementia (SDSVD) (WMD: − 2.15; 95 % CI: − 4.14 to − 0.16; P = 0.034), and National Institutes of Health stroke scale (NIHSS) (WMD: − 3.90; 95 % CI: − 4.87 to − 2.94; P < 0.001). Conclusions: Acupuncture is probably helpful in vascular stroke, but strong supportive data are not yet available. Acupuncture should be used cautiously, owing to the analysis of this study based on low to moderate evidence. Further high-quality, large-scale RCTs should be conducted.